Sustainable consumerism in the eyes of the Egyptian generation Z - Khalil, Salma (AUC Knowledge Fountain, 2020)
Sustainable Consumerism is a topic that is still being explored and developed across nations and countries. With the rising challenges of sustainable development, corporate sustainability maintains its position as being extremely challenging and difficult to achieve. Moreover, the new generation of consumers and the world’s future leaders – generation Z – have their characteristics and expectations that are expected to change the whole industrial scene to achieve sustainable development. Meanwhile, Egyptian generation Z remains unexplored and ambiguous. This study aims at studying the behavioral aspects of Egyptian generation Z, their consumerism, ecological consciousness, and corporate expectations. It adopts qualitative methods using in-depth semi-structured interviews with a selected sample of participants representing the intended target segment. The study findings are represented in a framework showing four layers of sustainability: awareness, motivation, action, and advocacy, with implications on the consumer, government, and private sector.